Macroeconomic Determinants of Liquidity of the Bond Market in Africa: Case Study of South Africa - Kapingura, Forget M (Journal of Economics and Behavioral Studies, 2015)
The importance of the bond market to the financial system and broader economy of a country cannot be underestimated. Thus this study seeks to establish the determinants of liquidity in the South African bond market using monthly data covering the period 1995 to 2009, employing the Johansen cointegration test and the Vector Error Correction Model. Empirical results reveal that there is a longterm relationship between the selected macroeconomic variables and bond market liquidity in South Africa. Based on the empirical results, it is recommended that authorities should keep inflation at low and stables levels as well as a stable currency. Of great importance in the study is the role played by foreign investors in the bond market. The positive impact of the foreign investor participation on the bond market liquidity in South Africa suggests that authorities should remove restrictions on foreign investor activities to enhance liquidity in this important market.